1993
DOI: 10.1111/j.1365-3024.1993.tb00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland material from the sand fly Lutzomyia longipalpis has an inhibitory effect on macrophage function in vitro

Abstract: Previous work from our laboratory demonstrated that the infectivity of the protozoan parasite Leishmania major was enhanced in mice if the infecting inoculum contained salivary gland lysates from the sand fly vector Lutzomyia longipalpis. The present study was designed to address the hypothesis that sand fly salivary gland material may function by inhibiting the host immune response. Results indicated that sand fly saliva inhibited the ability of macrophages to present leishmanial antigens to parasite-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 30 publications
2
57
0
2
Order By: Relevance
“…Although some Lu. longipalpis salivary components present immunomodulatory and anti-inflammatory properties [7,21,31], the development of DTH-like reactions to Lu. longipalpis SGS exposure in experimental models [25] and in individuals from endemic areas [19] suggests that these components elicit host-specific IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some Lu. longipalpis salivary components present immunomodulatory and anti-inflammatory properties [7,21,31], the development of DTH-like reactions to Lu. longipalpis SGS exposure in experimental models [25] and in individuals from endemic areas [19] suggests that these components elicit host-specific IR.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in vitro experiments demonstrate that SGS from Lu. longipalpis [20,21] or other sand fly species [22] modulates pro-inflammatory cytokine production as well as co-stimulatory molecule expression in human antigen-presenting cells [23], suggesting that SGS can impair host response against Leishmania. Although these data suggest that saliva components influence IR in vitro as well as in vivo in Leishmania-infected patients, the response to saliva in uninfected subjects in vivo has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…We did not investigate the mechanisms by which sand fly saliva inhibited release of chemotactic mediators, but it could be a consequence of macrophage inhibition of antigen presentation and also of the activity of CD4 + T-lymphocytes. This hypothesis is supported by studies that demonstrated that in a murine resistance model to leishmaniasis, the co-injection of SGE with Leishmania inhibits activation of T cells [50], as well as the oxidative burst [51], NO production [21,52] and antigen presentation [20] by macrophages. Furthermore, saliva also inhibited production of the proinflammatory cytokines, TNF-a, IFN-c and IL-12, enhancing the release of the anti-inflammatory mediators IL-4 and IL-10, in the focus of the Leishmania infection [23-25, 53, 54].…”
mentioning
confidence: 80%
“…Studies evaluating the effect of mosquito saliva on the immune response began relatively recently (Bissonnette et al 1993, Cross et al 1994, following the discovery that sand fly saliva enhanced infections with Leishmania major (Ribeiro 1989b, Theodos andTitus 1993). Early work described a factor in Ae.…”
Section: Modulation Of the Vertebrate Immune Response By Mosquito Salivamentioning
confidence: 99%
“…As described above, components of mosquito saliva have immunomodulatory activity, and thus, as a consequence, mosquito saliva can affect the anti-viral immune response and virus pathogenesis. Indeed, enhanced infection attributable to components of arthropod saliva is an accepted phenomenon, particularly with agents transmitted by ticks and sand flies (Cupp et al 1998, Edwards et al 1998, Limesand et al 2000, Nuttall and Labuda 2004, Theodos and Titus 1993. For example, when Leishmania major is inoculated with salivary gland extracts of sand flies, parasite burden, lesion size, and disease outcome are all amplified (Titus and Ribeiro 1988).…”
Section: Mosquito Associated Potentiation Of Arbovirus Transmission Amentioning
confidence: 99%